The fruits of knowledge co-creation in agriculture and food-related multi-stakeholder platforms in sub-Saharan Africa – A systematic literature review. (January 2021) - van Ewijk, Edith; Ros-Tonen, Mirjam A.F.
Abstract: Food insecurity and the weak position of smallholders in food value chains are key challenges in many low- and middle-income countries in sub-Saharan Africa. In order to increase food security and make agricultural value chains more inclusive, donors, governments and researchers increasingly stimulate partnerships between multiple actors, in which knowledge exchange, joint learning and knowledge co-creation play a central role in reducing the time lag between research findings and their translation into practical outcomes. Yet, despite the growing body of literature on multi-actor and cross-sector learning in these partnerships, an overview of existing literature and a strong evidence base of results of knowledge co-creation in these platforms is missing. Based on a systematic literature review, this paper documents existing evidence of knowledge co-creation processes in multi-stakeholder platforms (MSPs) in sub-Saharan Africa. Findings reveal, first, many examples of positive results, including increased yields and income for farmers; policy, regime and institutional changes; and changes in environmental sustainability. Second, there are several limitations to what MSPs can achieve, including limited attention for scaling up and a lack of sustainability due to dependency on donor funding. Third, there are limitations related to the evidence base: there is a tendency to report less on failures and available findings on the effectiveness of MSPs are mixed. Considering the evidence base, we conclude that there is a need to systematically document, report and assess MSPs and not take their effectiveness for granted. A systematic literature review thereby has an important added value because the critical assessment of methodological rigour increases the credibility of results documented in the included studies. Highlights: Multi-stakeholder platforms have positive impacts e.g. on farmers' income. Impacts are mainly on a local level, with limited linkages to higher scale levels. Sustainability of multi-stakeholder platforms at stake due to donor dependency. The review shows limited evidence of failures of platforms. Results on the effectiveness of multi-stakeholder platforms are mixed.